MODELING AND ANALYSIS OF FLOOD PREVENTION IN THE SUB-REGION OF BERINGIN RIVER FLOW, SEMARANG CITY - Widyanti Santosa, Wicke
The Beringin River is one of the rivers in Semarang which causes flood every year. Flood that inundated hundreds of houses in Semarang City were triggered by the breaking of the Beringin River embankment. Flood event is a phenomenon that occurs every year, where the factors that cause it are increasingly complex. This research modeled of the flooding that occurred in the Beringin watershed (DAS) by the help of ANUGA software (Australian National University and Geoscience Australia) in which the finite volume was used as a method, the modeling carried out would show the flood inundation that had occurred. And it will be studied with flood prevention efforts that occur in the Beringin watershed (DAS) using the Decision Support System (DSS). Decision making about the priority of handling the control of the Beringin river is analyzed by using the Analytical Hierarchy Process (AHP) method. From the results of the inundation modeling simulation, there was a flood distribution of Mangkang Wetan Village with flood height of 1- >4 meters covering 1.492188 hectares, Mangunharjo village with flood height of 1 - 3 meters covering an area of 5,6425.8 hectares, and Wonosari Village 1 - 4 meters wide 19400.76 hectares. So the total flooding with a height of 0 - 1 meter inundated an area of 55452 m2, flooding with a height of 1-2 meters inundated an area of 24690 m2, 2-3 meters covering an area of 8651 m2, height 3-4 meters inundated an area of 1766 m2. The method most desired by residents around the Beringin River in an effort to solve the flood of the Beringin River is the Normalization of the Beringin River. But the desire to execute river normalization was obstructed by land acquisition problems between the Semarang City Government and residents.